INSTITUSI-INSTITUSI ISLAM - Wan Ali Wan Jusoh, author 462853; Mohd. Hambali Rashid, author 609036; Muhammad Fathi Mohd Yusof, author 649666 (Kuala Lumpur [Pusat Pengajian Diploma], 2005)
Includes bibliography reference